Expression of the CTLA-4 ligand CD86 on plasmacytoid dendritic cells (pDC) predicts risk of disease recurrence after treatment discontinuation in CML - Schütz, Christian; Saußele, Susanne; Dietz, Christian; Müller, Martin Christian; Hehlmann, Rüdiger (Leukemia, 2017)
It is unknown, why only a minority of chronic myeloid leukemia (CML) patients sustains treatment free remission (TFR) after discontinuation of tyrosine kinase inhibitor (TKI) therapy in deep molecular remission (MR). Here we studied, whether expression of the T-cell inhibitory receptor (CTLA-4)-ligand CD86 (B7.2) on plasmacytoid dendritic cells (pDC) affects relapse risk after TKI cessation. CML patients in MR displayed significantly higher CD86+pDC frequencies than normal donors (P<0.0024), whereas TFR patients had consistently low CD86+pDC (n=12). This suggested that low CD86+pDC might be predictive of TFR. Indeed, in a prospective analysis of 122 patients discontinuing their TKI within the EURO-SKI trial, the one-year relapse-free survival (RFS) was 30.1% (95% CI 15.6-47.9) for patients with >95 CD86+pDC per 105 lymphocytes, but 70.0% (95% CI 59.3-78.3) for patients with <95 CD86+pDC (hazard ratio (HR) 3.4, 95%-CI: 1.9-6.0; P<0.0001). Moreover, only patients with <95 CD86+pDC derived a significant benefit from longer (>8 years) TKI exposure before discontinuation (HR 0.3, 95% CI 0.1-0.8; P=0.0263). High CD86+pDC counts significantly correlated with leukemia-specific CD8+ T-cell exhaustion (Spearman correlation: 0.74, 95%-CI: 0.21-0.92; P=0.0098). Our data demonstrate that CML patients with high CD86+pDC counts have a higher risk of relapse after TKI discontinuation.